2000
DOI: 10.1080/00779950009544315
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment and crime: New evidence for an old question

Abstract: This paper uses panel data techniques to examine the relationship between unemployment and a range of categories of crime in New Zealand. The data set covers sixteen regions over the period 1984 to 1996. Random and fixed effects models are estimated to investigate the possibility of a causal relationship between unemployment and crime. Hypothesis tests show that two-way fixed effects models should be used. The regression results provide some evidence for significant effects of unemployment on crime, both for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 15 publications
3
24
0
4
Order By: Relevance
“…Examples of panel-data research include Entorf and Spengler (2000) for Germany, Papps and Winkelmann (2000) for New Zealand, Machin and Meghir (2004) for the United Kingdom, Andresen (2013) for Canada, and Arvanites and Defina (2006), Ihlanfeldt (2007), , and Phillips and Land (2012) for the United States. With the exception of Papps and Winkelmann (2000), each of these papers finds at least some evidence in favor of a link between unemployment and crime, in particular, property crime. 38 Nonetheless, Chiricos's review also found that the unemployment-crime relationship was three times more likely to be positive than negative and fifteen times more likely to be positive and significant than negative and significant, indicating a basis for further research.…”
Section: Unemploymentmentioning
confidence: 99%
“…Examples of panel-data research include Entorf and Spengler (2000) for Germany, Papps and Winkelmann (2000) for New Zealand, Machin and Meghir (2004) for the United Kingdom, Andresen (2013) for Canada, and Arvanites and Defina (2006), Ihlanfeldt (2007), , and Phillips and Land (2012) for the United States. With the exception of Papps and Winkelmann (2000), each of these papers finds at least some evidence in favor of a link between unemployment and crime, in particular, property crime. 38 Nonetheless, Chiricos's review also found that the unemployment-crime relationship was three times more likely to be positive than negative and fifteen times more likely to be positive and significant than negative and significant, indicating a basis for further research.…”
Section: Unemploymentmentioning
confidence: 99%
“…However, these standard techniques are better suited to micro (short) panels with large N (number of units) and small T (number of years) that emphasize unit-specific heterogeneity and assume cross-sectional independence, whereas data used in crime-related fields are normally macro (long) panels with the unit dimension similar in size to the time dimension. Empirical studies in this area that use macro panels include Raphael and Winter-Ebmer (2001), Papps and Winkelmann (2000), Edmark (2005), Mehlum et al (2006), Mauser and Maki (2003), Rosenfeld and Fornango (2007), and Blais et al (2011) to mention a few, for which the average N is 16 and the average T is 23. When T is large, unobserved time-varying heterogeneity induced by common shocks will introduce cross-sectional dependence and can render the conventional pooled estimators inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…From a criminological perspective, the perpetration of a crime is caused by a myriad of factors such as situational circumstances [8,9], social context [24], and individual-level factors [29]. The complexity of both causes and effects of crime, which involves both micro-level and macro-level properties of social systems, emphasizes the need for an agent-based simulation framework to analyze crime and its causes.…”
Section: Introductionmentioning
confidence: 99%